Force de la pudeur - Suzanne Fraysse (Transatlantica)
This paper focuses on the strategic importance of sexuality in the abolitionist battle waged by slave narratives. The first whipping scene in Douglass’s 1845 autobiography is studied as an example of the way the almost unspeakable sexual tyranny of the masters manages to be suggested in spite of strict rules of narrative propriety. Other slave narratives are then examined to show how the slave narrators’ reticence does not simply stem from their desire to live up to the prudish expectations of their readers but constitutes a rhetorical strategy aiming at opposing fugitive slaves abiding by conservative moral values to slaveholders whose profligacy blurs the conventional boundaries between males and females, Blacks and Whites, animals and human beings. As a result, try as they may to challenge the scale of values associated with these stereotypes, slave narrators get trapped in a conservative system of polarities that define them as inferior. However, their desire to ingratiate themselves to their abolitionist readers should not be overestimated and the slave narrators’ reticence allows them to keep the inmost me behind a veil and elude the grasp of readers eager for sensational reporting.